A Study of Dopant Composition and Sintering Time Effect on Thermal Diffusivity of Doped and Undoped BSCCO Superconducting Ceramics - Liew, Josepine Ying Chyi; Mat Yunus, W. Mahmood; Abdul Wahab, Zaidan; Hamadneh, Imad; Shaari, Abdul Halim (Universiti Putra Malaysia Press, 2006)
In this paper, the undoped and Sm doped BSCCO superconducting ceramic samples prepared at various sintering times (i.e. 24, 48 and 100 hours) were investigated for their thermal diffusivity. The thermal diffusivity value was measured at room temperature using photoflash technique. The excitation source and detection system consisted of a high intensity camera flash and Ktype thermocouple. The measured thermal diffusivity value was found to be highly dependent on dopant concentration but not on sintering time. In this study, the surface morphology observed using Scanning Electron Microscopy (SEM) strongly supports the thermal diffusivity results.